Serum Neutralizing Activities from a Beijing Homosexual Male Cohort Infected with Different Subtypes of HIV-1 in China - Zhang, Mingshun (Public Library of Science, 2012)
Protective antibodies play a critical role in an effective HIV vaccine; however, eliciting antibodies to block infection by viruses from diverse genetic subtypes remains a major challenge. As the world’s most populous country, China has been under the threat of at least three major subtypes of circulating HIV-1 viruses. Understanding the cross reactivity and specificities of serum antibody responses that mediate broad neutralization of the virus in HIV-1 infected Chinese patients will provide valuable information for the design of vaccines to prevent HIV-1 transmission in China. Sera from a cohort of homosexual men, who have been managed by a major HIV clinical center in Beijing, China, were analyzed for cross-sectional neutralizing activities against pseudotyped viruses expressing Env antigens of the major subtype viruses (AE, BC and B subtypes) circulating in China. Neutralizing activities in infected patients’ blood were most capable of neutralizing viruses in the homologous subtype; however, a subset of blood samples was able to achieve broad neutralizing activities across different subtypes. Such cross neutralizing activity took 1–2 years to develop and CD4 binding site antibodies were critical components in these blood samples. Our study confirmed the presence of broadly neutralizing sera in China’s HIV-1 patient population. Understanding the specificity and breadth of these neutralizing activities can guide efforts for the development of HIV vaccines against major HIV-1 viruses in China.